2016
DOI: 10.1038/micronano.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-tunable dual-layer terahertz metamaterials

Abstract: This paper presents the design, fabrication, and characterization of a real-time voltage-tunable terahertz metamaterial based on microelectromechanical systems and broadside-coupled split-ring resonators. In our metamaterial, the magnetic and electric interactions between the coupled resonators are modulated by a comb-drive actuator, which provides continuous lateral shifting between the coupled resonators by up to 20 μm. For these strongly coupled split-ring resonators, both a symmetric mode and an anti-symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…Although a number of THz tunable transmission filters based on MEMS-driven metamaterials have been demonstrated [19][20][21][22][23][24][25][26][27][28][29][30][31] , the realization of a high-performance MEMS-driven tunable THz absorber is still challenging, and only a limited number of demonstrations have been reported so far 32 . This low number is primarily due to the severe mismatch between the actuation range of most MEMS (on the scale of 1-10 μm) and THz wavelengths on the scales of 100-1000 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of THz tunable transmission filters based on MEMS-driven metamaterials have been demonstrated [19][20][21][22][23][24][25][26][27][28][29][30][31] , the realization of a high-performance MEMS-driven tunable THz absorber is still challenging, and only a limited number of demonstrations have been reported so far 32 . This low number is primarily due to the severe mismatch between the actuation range of most MEMS (on the scale of 1-10 μm) and THz wavelengths on the scales of 100-1000 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods to make a relative displacement between closely placed pair of meta-atoms or pair of metasurfaces have been reported. [13][14][15][16][17][18][19][20][21][22][23][24] When two (or more) meta-atoms are placed close enough to couple via near-field interactions, new resonant modes can be supported akin to bonding and antibonding molecular orbitals in molecular systems. These new resonant modes are quite sensitive to the relative position and/or orientation of meta-atoms and therefore can give a mechanism to tune the resonant frequency by giving a relative displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Similar mechanisms can apply to layered arrays of meta-atoms or metasurfaces. Recently, such active tuning has been experimentally realized by slightly shifting relative position of double-layered metamaterials utilizing π-conjugated polymer actuators, 22 MEMS actuators, 23 or microcantilever. 24 We recently demonstrated that double-layered closed-ring resonator (CRR) arrays are capable of relatively large tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the design and fabrication of planar THz metamaterials and modulators based on them have been discussed intensively. Ref [16][17][18][19][20][21][22][23][24] suggested us the possibilities for successful implementation of proposed metamaterials in future.…”
mentioning
confidence: 99%
“…The metamaterials with incorporated silicon or gallium arsenide inclusions were discussed in details as elements of modulators. The phase tunability, blueshift, redshift as well as amplitude switching shown in THz frequency range [16][17][18][19][20][21][22][23][24]. Although the semiconductor inclusions play the role of capacitor elements or as the tunable metamaterial substrate.…”
mentioning
confidence: 99%